2006
DOI: 10.1002/pros.20435
|View full text |Cite
|
Sign up to set email alerts
|

Effective treatment of mouse metastatic prostate cancer by low electric field enhanced chemotherapy

Abstract: Our results suggest that LEFCT-EC is an effective method for the destruction of metastatic prostate tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Our results agreed with those of previous studies . Our results were also supported by the basic research studies that have shown that CT or radiotherapy is more effective in immunocompetent mice than in immunodeficient mice and that immunosuppression counteracts the effect of CRT . The attraction of increased numbers of TILs before neoadjuvant treatment was reported to imply that a tumor was originally immunogenic .…”
Section: Discussionsupporting
confidence: 92%
“…Our results agreed with those of previous studies . Our results were also supported by the basic research studies that have shown that CT or radiotherapy is more effective in immunocompetent mice than in immunodeficient mice and that immunosuppression counteracts the effect of CRT . The attraction of increased numbers of TILs before neoadjuvant treatment was reported to imply that a tumor was originally immunogenic .…”
Section: Discussionsupporting
confidence: 92%
“…39 These locally amplified fields are thought to inhibit cell proliferation. 39 The enhancement of the chemotherapeutic effect by electric fields, electrochemotherapy, [40][41][42][43] is believed to result from the synergy between the chemotherapeutic drug and field-induced electroporation of metastatic cell membranes. 43 The model reaction studied in this paper, the double proton transfer in the formic acid dimer (or related dimers), has been studied primarily in the absence of external fields.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, preclinical studies have demonstrated that the density of CD4+ and CD8+TILs is positively associated with good response after RT, CT and CRT [42]. Furthermore, basic studies of breast and prostate cancer suggest that RT or CT may be more sufficient in immunocompetent mice than immunosuppressive ones [43, 44]. We have found that the addition of CT to RT can not significantly improve OS in the low risk group.…”
Section: Discussionmentioning
confidence: 86%